Mempertimbangkan Perbedaan Penilaian Formatif Dan Penilaian Sumatif Dalam Kurikulum Mandiri - Anis Fatkhulilah; Lu'luil Maknun (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the differences between the use of formative and summative assessments in the Merdeka Curriculum. The method used is a literature review, examining various national and international sources related to the concepts, implementation, and results of previous research. The results of this review indicate that formative assessment emphasizes providing constant feedback, thereby helping teachers and students improve the teaching and learning process directly. In contrast, summative assessment serves as a final evaluation to measure students' learning achievements. The comparison between these two types of assessment indicates that a balanced combination of formative and summative assessments can create a learning environment that is more responsive, participatory, and aligned with the principles of the Merdeka Curriculum. The limitation of this study lies in the type of data used, which comes from secondary sources, so the results obtained are theoretical and have not yet been supported by direct empirical data from the field. The new element offered by this study is the comparative analysis of the two types of assessment within the context of Indonesia's relatively new education policy. The recommendations proposed include improving teachers' understanding of assessment concepts, developing relevant evaluation tools, and providing continuous policy support. Thus, this study makes an important contribution to strengthening learning assessment practices within the Merdeka Curriculum.